The Relationship between Ethnochemistry Learning Experience and Cognitive Learning Outcomes Based on Gender - Dwi Wahyudiati (Graduate School of Universitas Negeri Malang, 2023)
This study analyzes the relationship between ethnochemistry learning experiences and students’ cognitive learning outcomes based on gender perspective. This quantitative study adopted the survey design. The sample of 60 people (40 women and 20 men) was determined through cluster random sampling. An ethnochemistry-based learning experience questionnaire and student cognitive learning outcomes tests were utilized to collect the data. The collected data were then analyzed by multiple regression test with a significance level of .05. The conclusion drawn based on the results were; 1) the cognitive learning outcomes of chemistry students are higher than the ethnochemistry-based learning experience, and 2) there is a significant relationship between the ethnochemistry learning experience and the students’ cognitive learning outcomes in terms of gender perspective